An extract from pork bones containing osteocalcin improves glucose metabolism in mice by oral administration. Issue 11 (1st November 2016) - Mizokami, Akiko; Wang, DaGuang; Tanaka, Mitsuru; Gao, Jing; Takeuchi, Hiroshi; Matsui, Toshiro; Hirata, Masato
Abstract: Osteocalcin (OC) is a bone-derived hormone that regulates energy metabolism. OC exists in two forms, carboxylated (GlaOC) and uncaboxylated (GluOC), but only the latter appears to have an endocrine function. In this study, we prepared an extract containing both Gla- and GluOC from boiled pork bone using 0.2 M carbonate buffer at pH 9.5, and tested whether the extract had beneficial effects on improving metabolic parameters in obese mice. The extract equivalent of 1.2 μg of GluOC/mouse was orally administrated to C57BL/6 female mice fed a high-fat, high-sucrose diet. Daily oral administration of the extract for four weeks decreased blood glucose levels and promoted glucose tolerance as well as insulin sensitivity. Our study shows for the first time that boiled pork bones are a source material for osteocalcin in the large-scale production of supplements designed to improve glucose metabolism. Graphical abstract: : Oral administration of osteocalcin extracted from pork bone improves metabolic state in mice fed a high-fat, high-sucrose diet.